KOMUNIKASI DAKWAH KOLABORATIF PEMERINTAH DESA MELALUI KEBIJAKAN PUBLIK - Miftahul Huda; Muhammad Ulin Nuha; Dewi Mashfufah (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
Margoyoso Jepara village is a village that has socio-religious problems as part of the negative impact of the times. Under these conditions, the Village Government carried out collaborative da'wah communication in overcoming these problems. This type of research is qualitative with field research methods. In this study, data collection techniques through interviews, observation, and documentation. Data analysis techniques used in the form of inductive and descriptive narrative. The results of this study explain that collaborative da'wah in the Margoyoso Village Government is influenced by the existence of a village autonomy system, where the Village Government can manage and regulate its own government area according to the characteristics and styles of each. The emergence of collaborative da'wah policies is motivated by social and political religious problems. The message of Da'wah communication in the form of congregational dawn prayers, turning off the television after sunset, let's recite the Koran, and compulsory madrasah diniyah was formed through a deliberation process by the Village Government, community leaders, religious leaders, socio-religious organizations, and related stakeholders. Collaborative da'wah policy has benefits as a means to strengthen friendship with residents, a means of socialization and village information, as well as a means to improve the quality of religion and community education.